La cocina de inducción como herramienta didáctica para potenciar el aprendizaje de electromagnetismo en los estudiantes del segundo año del BGU del colegio fisco-misional Vicente Anda Aguirre de la parroquia El Sagrario de la ciudad de Loja, período 2015 – 2016 - Vinces Vinces, Fabricio Vladimir (2015)
The present research focuses on the study of: INDUCTION COOKER AS EDUCATIONAL TOOL TO ENHANCE ELECTROMAGNETISM LEARNING IN SECOND YEAR STUDENTS AT ANDA AGUIRRE VICENTE HIGH SCHOOL IN THE PARISH “EL SAGRARIO” OF LOJA CITY, 2015 -2016 PERIOD; with the principle goal to take advantage of the importance of this electronic device as a teaching tool to improve the learning of electromagnetism in the second year students at Vicente Anda Aguirre high school parish “el Sagrario” the Loja city, 2015 – 2016 period . The research responded to a descriptive and pre-experimental design, in other words the researcher administered a pretest and a posttest, the first one (pretest) was conducted before applied the workshop and the posttest at the end of the workshop. It is important to mention that the pretest and posttest are the same; the phases used of this research were: comprehensive, diagnostic phase, the development and application of: models, educational workshops and evaluation of the effectiveness which was made using Wilcoxon rank sign test; this process was conducted with a population of 2 teachers and 30 students of second year of BGU. The main findings, needs, and difficulties in students can be reduced by applying the alternative of induction cooker as a teaching tool, for being an innovative and direct medium and a technological application from electromagnetism